Relationship Between Compassion Fatigue in Nurses, and Work-Related Stress and the Meaning of Life - Aslan, Hakime; Erci, Behice; Pekince, Hatice (Springer, 2022)
This research was conducted in order to examine the correlation between work-related stress and meaning of life in association with compassion fatigue of nurses, as well as to determine the factors that affect compassion fatigue. The research is cross-sectional. The population of the research is comprised of nurses working at a university hospital in the east of Turkey. The research was carried out with 336 nurses. Introductory information form, Work-related strain inventory, Professional quality of life scale and compassion fatigue subscale and Life attitude profile were used for data collection. It was identified that correlation between compassion fatigue and attitude to life profile is negative (r = -.542**, p = 0.000), while the correlation between work-related stress and compassion fatigue is positive (r = .204**, p = 0.000). Moreover, it was determined that attitude to life profile, work-related stress, work manner, amount of time working at one occupation, service held and gender have effect on compassion fatigue.
Keywords: Compassion fatigue; Stress; Meaning of life; Nurse